Inovasi Pembelajaran Bahasa Arab Berbasis Multiple Intelligences - fajaruddin, Aris; Jannah, Raudlatul; Ibermarza (Universitas Nahdlatul Ulama Pasuruan, 2023)
Learning Arabic as a foreign language requires innovative efforts. Innovative efforts in learning Arabic are a challenge for educators to be able to develop students' intelligence. The diverse character of students is important to be able to mix and match learning methods. The delivery of material in learning must be able to pay attention to the diversity of intelligence of students. That's why in this study the researchers wanted to convey Arabic language learning innovations based on Multiple intelligence.